TEKNIK DAN APLIKASI OLAHAN LIMBAH AIR KELAPA MENJADI PUPUK ORGANIK CAIR GUNA MENINGKATKAN PRODUKSI TANAMAN - Jasmi Jasmi; Huri Afrina Dewi; Putra Susila; Aristotel Gunawan; Rosmeri Rosmeri (Jurnal Pengabdian Agro and Marine Industry, 2021)
Even though coconut water is considered as agricultural waste, if it can be utilized properly it will be a source of income for the community, as well as fertilizer for soil enrichment. Therefore, with the abundance of coconut water waste, it is necessary to disseminate information to the community of farmer groups in the form of counseling about techniques and their application to soil and plants, to provide many benefits for the community and for the surrounding environment. Liquid organic fertilizer (POC) is one type of fertilizer that is widely circulated in the market. Liquid organic fertilizers are mostly applied through the leaves or referred to as foliar liquid fertilizers which contain essential macro and micro nutrients N, P, K, S, Ca, Mg, B, Mo, Cu, Fe, Mn, and organic matter